Do Patient-specific or Fracture-specific Factors Predict the Development of Acute Compartment Syndrome After Pediatric Tibial Shaft Fractures?. Issue 3 (March 2020) - Villarreal, Eric D.; Wrenn, Jesse O.; Sheffer, Benjamin W.; Sawyer, Jeffrey R.; Spence, David D.; Kelly, Derek M.
Abstract : Background: Tibial shaft fractures are the most common injuries preceding acute compartment syndrome (ACS), so it is important to understand the incidence of and risk factors for ACS after pediatric tibial shaft fractures. The purposes of this study were to determine the rate at which ACS occurs and if any patient or fracture characteristics are significantly associated with developing ACS. Methods: All patients aged 5 to 17 years treated for a tibial shaft fracture at a level 1 pediatric trauma center, a level 1 adult trauma center, and an outpatient orthopaedic practice between 2008 and 2016 were retrospectively identified. Demographics, mechanisms of injury, and fracture characteristics were collected from the medical records. Radiographs were reviewed by study authors. ACS was diagnosed clinically or by intracompartmental pressure measurement. Univariable analysis was performed using the Fisher exact test for nominal variables and simple logistic regression for continuous variables. Multivariable analysis was performed using stepwise logistic regression. Results: Among 515 patients with 517 tibial shaft fractures, 9 patients (1.7%) with 10 (1.9%) fractures developed ACS at a mean age of 15.2 years compared with a mean age of 11 years in patients without ACS ( P =0.001). One patient with bilateral tibial fractures developed ACS bilaterally. Age greater than 14 years ( P =0.006), higher body mass index ( P <0.001), motorcycle or motor vehicle accidents ( P =0.034), comminuted and segmental tibial shaft fractures ( P <0.001), ipsilateral fibular fracture ( P =0.002), and associated orthopaedic injuries ( P =0.032) were all significantly more common in the ACS group. Conclusions: ACS developed in 1.7% of the patients with tibial shaft fractures in this retrospective study—a rate significantly lower than previously reported. Age greater than 14 years, higher body mass index, motor vehicle or motorcycle accidents, comminuted or segmental fracture pattern, ipsilateral fibular fracture, and associated orthopaedic injuries are all significantly associated with its development. Levels of Evidence: Level III—retrospective comparative study.